Tindakan Trabekulektomi pada Pasien dengan Glaukoma Sudut Tertutup Primer Unilateral – Laporan Kasus - Wenny Supit (Universitas Sam Ratulangi, 2023)
Abstract: Primary angle closure glaucoma (PACG) is the leading cause of blindness in Asia. In PACG, degenerative changes in the trabecular meshwork resulting from iridiotrabecular contact (ITC) cause high intraocular pressure resulting in glaucomatous optic atrophy. We reported a 58-year-old woman came with the chief complaint of pain in the right eye for three months, accompanied by red and watery eye, and glare when exposed to light. Patient also complained of headaches and sometimes nausea. There was a history of hypertension since one year ago, but not taking any drugs. In ophthalmological examination of the right eye, visual acuity was 6/20, intraocular pressure 39 mm Hg, conjunctival injection, corneal edema, Van Herick 1 shallow anterior chamber, iris atrophy, round shaped and centrally located pupil with a diameter of 5 mm and a NO3NC3 lens. In the posterior segment of the right eye, non-uniform fundal reflexes were found, papillae were round, vital, well-defined with a cup and disc ratio of 0.7-0.8. The patient was diagnosed with primary angle-closure glaucoma in the right eye and a trabeculectomy was performed on the right eye. After trabeculectomy, the intraocular pressure of the right eye was 17.7 mm Hg. In conclusion, trabeculectomy has a high success rate in terms of controlling intraocular pressure in primary angle closure glaucoma. Keywords: glaucoma; primary angle closure; tabeculectomy Abstrak: Glaukoma penutupan sudut primer (PACG) merupakan penyebab utama kebutaan di Asia. Pada PACG, perubahan degeneratif dalam trabecular meshwork yang dihasilkan dari kontak iridiotrabecular (ITC) menyebabkan tekanan intraokular tinggi yang menghasilkan glaucomatous optic atrophy. Kami melaporkan kasus eorang perempuan berusia 58 tahun datang dengan keluhan nyeri mata kanan sejak tiga bulan yang lalu, disertai dengan mata merah, berair dan silau saat terkena cahaya. Pasien juga mengeluh adanya nyeri kepala dan kadang disertai mual. Riwayat hipertensi sejak satu tahun sebelumnya, tidak mengonsumsi obat-obatan. Pada pemeriksaan oftalmologi mata kanan didapatkan visus 6/20, tekanan intraokuler 39 mmHg, konjungtiva injeksi, kornea edema, bilik mata depan dangkal Van Herick 1, iris atrofi, pupil berbentuk bulat letak sentral dengan diameter 5 mm serta lensa NO3NC3. Pada segmen posterior mata kanan ditemukan refleks fundus non uniform, papil bulat, vital, berbatas tegas dengan cup and disc ratio 0,7-0,8. Pasien didiagnosis dengan glaukoma sudut tertutup primer mata kanan dan dilakukan tindakan trabekulektomi pada mata kanan. Setelah tindakan trabekulektomi, tekanan intraokuler mata kanan menjadi 17,7 mmHg. Simpulan kasus ini ialah trabekulektomi terbukti memiliki tingkat keberhasilan yang tinggi dalam hal mengontrol tekanan intraokuler pada glaukoma penutupan sudut primer. Kata kunci: glaukoma; sudut tertutup primer; trabekulektomi